2020
DOI: 10.1002/app.49597
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the microstructure and enzymatic hydrolysis performance of chitin treated by steam explosion, high‐pressure homogenization, and γ radiation

Abstract: This research intends to reduce the crystallinity of chitin with physical methods so as to improve the enzymatic hydrolysis efficiency of chitin. Scanning electron microscopy showed that both steam explosion and high‐pressure homogenization significantly enlarged the pores in shrimp shells, which are made up of chitin, but γ radiation did not. X‐ray diffraction showed that the crystallinity index of chitin decreased by 23.2% in the (110) plane and 24.7% in the (020) plane after three rounds of steam explosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Crayfish are one of the most important raw materials for commercial chitin 25 . High‐pressure treatment can reduce the crystallinity of chitin, thereby leading to easier crayfish peeling 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crayfish are one of the most important raw materials for commercial chitin 25 . High‐pressure treatment can reduce the crystallinity of chitin, thereby leading to easier crayfish peeling 26 …”
Section: Resultsmentioning
confidence: 99%
“…25 High-pressure treatment can reduce the crystallinity of chitin, thereby leading to easier crayfish peeling. 26…”
Section: Normalization Of Peeling Workmentioning
confidence: 99%
“…Studies have shown that ultrasound can enhance the binding ability of chitinase and chitin, with the maximum binding force of 105.33 ± 23.51 pN and the loading speed at 0.3 μm/s [59]. In addition, steam explosion was also used for the pretreatment of chitin, which reduced the crystallinity of chitin through the generated pressure and thermal effects, thus improving the efficiency of enzymatic degradation [60,61].…”
Section: Physical Methodsmentioning
confidence: 99%
“…The final products hydrolyzed from 1 g of treated chitin were 0.1 g (GlcNAc) 2 and (Glc-NAc) 3 . Ultrasonic treatment, steam explosion, and ball milling were also used for the pretreatment of chitin to assist in enzymatic degradation [56,[59][60][61]. In addition, microbial fermentation is also an effective way to pretreat chitin, which can greatly reduce the crystallinity and MW of chitin and is more conducive to the hydrolysis of chitinase [78].…”
Section: Enzymatic Methodsmentioning
confidence: 99%
“…Since cricket powder contains chitin, the impact of HPH on this constituent is also very important. In fact, HPH treatment (60-80 MPa) can reduce the crystallinity and improve enzymatic hydrolysis efficiency of chitin increasing the concentration of N-Acetyl-glucosamine [19,20].…”
Section: Introductionmentioning
confidence: 99%